PENGARUH PENERAPAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN INVERTEBRATA DI KELAS X SMA SWASTA PERSIAPAN STABAT - Ummul Khairunnisa; Melva Silitonga (Jurnal Pelita Pendidikan, 2017)
This research aim to get information about the effect of contextual teaching learning ininvertebrate base material in X class SMA SWASTA PERSIAPAN STABAT 2014/2015. This research isexperiment research by using objective test as the equipment to get data of the research.Population in this research are all the student in X class SMA SWASTA PERSIAPAN STABAT in2014/2015 year. That consist of four class and the total of the student 160. Student mean while thesample of this research taken by random groups and share in to two class, where the class makeas the experiment class and the total of student in this class are 40 students. And class make assupervise class by conventional style with the total student are 40 students. So the total of examplein this research are 80 students. Based on data test, both in student study result in experiment classand supervise class declaration normal distribution and have the same variant mean while based onthe analysis data research result, can look. There are differences of study result that significantbetween experiment class and supervise class, where the average of student study result inexperiment class is 80,2 mean while the student study result in supervise class is 74,6. The differenceof the student study result also proved throw hypothesis test by using test- t and believe quality α=0,05. Where > (2,60 > 1,99) its mean in this research rejected and also received .Mean while the research of classically around 90%, so it’s concluded the research of finishing in contextual teaching learning to the student study result in base material invertebrate X class SMASWASTA PERSIAPAN STABAT 2014/2015.Keyword : Contextual Teaching Learning, Biology Student Study Result